THE EFFECT OF MODERNIZATION OF TAX ADMINISTRATIVE SYSTEM, QUALITY OF SERVICE, TAX KNOWLEDGE ON TAXPAYER COMPLIANCE (Empirical Study of Taxpayers at KPP Pratama East Semarang) - Mustakim, Khanif Satriani Citra; Ratnawati, Juli (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2023)
Tax is a mandatory contribution from the public to the state. This study aims to determine whether there is influence between the modernization of the administrative system, service quality, and knowledge of taxation on taxpayer compliance at KPP Pratama East Semarang. The data used in this study is primary data, and the sampling technique is simple random sampling. The sample of this research is 100 taxpayer respondents at KPP Pratama East Semarang. Analysis of research data using SPSS software. While the results of this study indicate that modernization of the administrative system has a positive but not significant effect on taxpayer compliance at KPP Pratama East Semarang, service quality has no effect and is not significant on taxpayer compliance at KPP Pratama East Semarang, and knowledge of taxation has a significant positive effect on compliance taxpayer.